Depressive-anxious disorders in clinical picture of bronchial asthma combined with erosive-ulcerous affections of gastroduodenal zone - Ye. A. Ustjuzhanina; G. M. Chernyavskaya; E. I. Beloborodova; N. A. Kornetov (Бюллетень сибирской медицины)
In the paper a popularity frequency and peculiarities of depressive-troubled disorder (DAD) course at patients with bronchial asthma (BA) have been estimated depending on the presence of associated erosive-ulcerous affections of gastroduodenal zone (EUA GDZ) and an impact of DAD on BA course has been studied. Depressive-anxious disorders have been revealed at 87 (78%) of 112 interrogated patients, most of them had the depression of medium degree that had required a therapy with the possible antidepressant use. Combined disorders in the form of depression and anxiety prevailed. It has been found that persons of the older age were subjected to the risk of DAD development. Patients with mixed pathology had more expressed DAD.